2012
DOI: 10.1108/17561391211200920
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge management capabilities and SMEs' organizational performance

Abstract: PurposeThe purpose of this paper is to examine the role of knowledge management (KM) capabilities on small to medium‐sized enterprises' (SMEs') organizational performance.Design/methodology/approachIn this study, Data were collected from 30 SMEs in Iran. The present study employs a questionnaire survey approach to collect data for testing the research hypotheses. The response rate was 60 percent. Relevant statistical analytical techniques, including regression for analysis, were then used.FindingsThe results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
97
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(108 citation statements)
references
References 82 publications
(75 reference statements)
8
97
0
3
Order By: Relevance
“…The positive association of HRM practices and KM was also asserted by Theriou and Chatzoglou (2014), Kuo (2011) and Donate and Guadamillas (2011). Furthermore, Shehata (2015), Gharakhani and Mousakhani (2012), Marqués and Simón (2011), Zack et al (2009), Mills and Smith (2011 and Kuo (2011) confirmed the significant impact of KM on OP.…”
Section: Hypotheses Testingsupporting
confidence: 52%
“…The positive association of HRM practices and KM was also asserted by Theriou and Chatzoglou (2014), Kuo (2011) and Donate and Guadamillas (2011). Furthermore, Shehata (2015), Gharakhani and Mousakhani (2012), Marqués and Simón (2011), Zack et al (2009), Mills and Smith (2011 and Kuo (2011) confirmed the significant impact of KM on OP.…”
Section: Hypotheses Testingsupporting
confidence: 52%
“…Crosby referred to it as the price of nonconformance. Gharakhani et al (2013) stated that the cost of prevention is less than the cost of correction. In addition, any compromise on quality by SMEs could also jeopardize the supply chain, resulting in raising costs because of poor quality (Kumar, 2007).…”
Section: Total Quality Management: the Cost And Success Of Its Practimentioning
confidence: 99%
“…Gharakhani et al (2013) explained that the cost of quality is considered by both Crosby and Juran to be the primary tool for measuring quality. The cost implication of not adopting TQM is relevant for the explanation of little or no growth or entropy of some SMEs within the shortest period of start-up.…”
Section: Total Quality Management: the Cost And Success Of Its Practimentioning
confidence: 99%
See 1 more Smart Citation
“…Gharakhani et al (2013) states that Quality Management has long been established as an important tool for achieving competitive advantage. The customer has taken the center stage and organization's ability to adapt to ever changing customer requirements has become extremely important for long-term success.…”
Section: Introductionmentioning
confidence: 99%